Numerical Simulation of Deep Coalbed Methane Development Based on Embedded Discrete Fracture Model: A Triple Medium Flow Approach - Yongsheng An; Zhongwen Sun; Jin Wang; Xiaoyu Zhang; Yangfeng Sun (Energy Science & Engineering)
ABSTRACT China is rich in coalbed methane resources, especially with significant potential for deep coalbed methane development. As shallow coalbed methane resources gradually deplete, the development of deep coalbed methane has become a research focus. Due to the low permeability and micro‐scale migration characteristics of deep coalbed methane, its exploitation requires different approaches compared to shallow coalbed methane. This paper, based on the embedded discrete fracture numerical simulation technology used for shale gas, considering the shrinkage effect of coal matrix, establishes a triple‐medium flow model comprising cleats, natural fractures, and artificial fractures to simulate the deep coalbed methane extraction process. When compared with traditional numerical simulation methods using real well data, the new model improves accuracy by 8.08%. The sensitivity analysis of engineering parameters and geological parameters in the development of deep coalbed methane reveals that the gas content coal seams are the main factors affecting gas production. To obtain high‐yield gas wells, it is necessary to create a complex hydraulic pressure fracture network in high gas content layers. This study provides a new numerical simulation model for deep coalbed methane development. The model couples cleats, natural fracture networks, and fractures, and accurately represents the geological characteristics of deep coalbed methane reservoirs. Additionally, this study provides theoretical support for improving the production of deep coalbed methane through one‐factor sensitivity analysis.